Prevalence of non-carious cervical injuries in young adults and cervical dentin hypersesitivity at the School of Dentistry of Recife (Research, Society and Development, 2022)
The objective of this research was to estimate the prevalence of non-carious cervical lesions (NCCL) and cervical dentinal hypersensitivity (HDC) in young adults from the population of Recife, pointing out the percentage of LCNC´s and HDC in the individuals surveyed, socioeconomic and demographic profile and highlighting the situational diagnosis of NCCL ´s and HDC for the studied population. Sixty patients were examined at the teaching clinic of Faculdade de Odontologia do Recife-FOR, using a questionnaire as an instrument for data collection.Clinical examination was used to verify the presence of lesions on the buccal surface of premolars and first molars of all quadrants, in addition to Cervical Dentin Hypersensitivity. Clinical examination was used to verify the presence of NCCL's, in addition to Cervical Dentin Hypersensitivity. Data were descriptively analyzed using absolute frequencies and percentages for categorical variables and measures: mean, standard deviation and median for the age variable, and the results were presented in tables containing the values obtained in the survey of the questionnaires. Of the 60 patients, the majority (55.0%) stated that they used to eat acidic foods and that this occurrence is probably due to a change in eating habits and lifestyle. Although the prevalence of NCCL is increasing with age, in the present study, it was not possible to observe this prevalence, as only 5.0% of the 60 patients surveyed had LCNC and 13.3% had HD.